The Differential Role of Coping, Physical Activity, and Mindfulness in College Student Adjustment - Moeller, Robert W.; Seehuus, Martin; Simonds, Jack; Lorton, Eleanor; Randle, Terumi Smith; Richter, Cecilia; Peisch, Virginia (Frontiers in Psychology, 2020)
Research has examined the function of stress management techniques, including coping, physical activity, and mindfulness on college students’ adjustment. The present study examined the differential contributions of three stress management techniques to students’ maladaptation (perceived stress, depression, anxiety, loneliness) and adaptation (self-esteem). Undergraduate students (N = 1,185) responded to an online survey. Hierarchical linear regression results indicated that all three stress management techniques—coping, physical activity, and mindfulness—were related to the five outcomes as predicted. Higher levels of disengagement coping strategies were related to higher perceived stress, anxiety, and depression. Mindfulness emerged as a strong predictor of adaptation